Court Street from Scollay Square, July 15, 1897 - Boston Transit Company (Tufts Archival Research Center, 2005)
Elevated view north-northwest of Court Street from Scollay Square. Buildings line both the east-northeast and west-southwest sides of the street. Signage and awnings adorn the facades of most of the buildings included in the photograph. The Crawford House, located at 83 Court Street on the northeast corner of Court and Brattle Streets, is included in the upper-right corner of the photograph. Electricity lines and poles line Court Street and Scollay Square, and street railroad cars and pedestrians are included in the photograph. A statue of John Winthrop, located in the center of Scollay Square, is included in the lower-right corner of the photograph. Printed by The Heliotype Printing Company of Boston 4 1/4 x 6 1/2, 4 13/16 x 6 7/8 overall Photomechanical prints